Demokrasi Desa Dalam Pemilihan Kepala Kampung Tahun 2021 Long Bagun Ilir Di Kabupaten Mahakam Ulu - Ignatius Refli Pangestu Passarella; Mohammad Taufik (Jurnal Ilmu Pemerintahan, 2023)
This research analyzes the presentation of research data in the reportof the 2021 Village Chief Election in Mahakam Ulu Regency. The focusof this research is on the stages of preparation and nomination in thesimultaneous election of village leaders. The preparation stages includethe final delivery of the village leaders' term and the formation of theelection committee. The nomination stages involve announcements,registration of prospective candidates, research on administrativerequirements, clarification, designation, and announcement ofcandidates. Challenges were found, such as the low number ofcandidate registrants that need further socialization to the community.The research results indicate that the presentation of research datathrough the stages of preparation and nomination involves theimportant role of the election committee. The committee is responsiblefor planning, supervising, and executing all stages of the election. Theencountered challenge is the low number of candidate registrants,requiring intensive socialization efforts. To enhance the presentationof research data in the future, steps need to be taken, such as expandingcommunity participation in nominations, improving understanding ofthe nomination process and requirements, and strengthening the roleof the election committee. This is expected to support a more effectiveand inclusive implementation of village democracy.